Economically Improving the quality of construction through Six Sigma and Cost Benefit Analysis. Issue 1 (1st December 2022) - Aswin, Bharath A; Saravanan, M; Ramakrishnan, S; Adhithiya Varma, B; Mounish, S
Abstract: Six Sigma is a quality management tool which is highly effective in manufacturing industries, but implementing the six sigma in construction sector is a challenging task since each and every construction project is involved with huge quantity of money. As we all know that the quality and the cost of the constriction project are directly proportional to each other, so in the attempt of improving the quality of the project, we also end up in exceeding the budgeted cost of the project. To avoid this situation in the construction projects, the quality management tool six sigma is combined with a cost management tool Cost Benefit Analysis. This study shows the method of improving the quality of the construction process without affecting the cost of the construction. Combination of these two management tools provided an organization with a successful quality project with budgeted cost.